Regulation of early adipose commitment by Zfp521. - Sona Kang; Peter Akerblad; Riku Kiviranta; Rana K Gupta; Shingo Kajimura; Michael J Griffin; Jie Min; Roland Baron; Evan D Rosen (PLoS Biology)
While there has been significant progress in determining the transcriptional cascade involved in terminal adipocyte differentiation, less is known about early events leading to lineage commitment and cell fate choice. It has been recently discovered that zinc finger protein 423 (Zfp423) is an early actor in adipose determination. Here, we show that a close paralog of Zfp423, Zfp521, acts as a key regulator of adipose commitment and differentiation in vitro and in vivo. Zfp521 exerts its actions by binding to early B cell factor 1 (Ebf1), a transcription factor required for the generation of adipocyte progenitors, and inhibiting the expression of Zfp423. Overexpression of Zfp521 in cells greatly inhibits adipogenic potential, whereas RNAi-mediated knock-down or genetic ablation of Zfp521 enhances differentiation. In addition, Zfp521⁻/⁻ embryos exhibit increased mass of interscapular brown adipose tissue and subcutaneous white adipocytes, a cell autonomous effect. Finally, Ebf1 participates in a negative feedback loop to repress Zfp521 as differentiation proceeds. Because Zfp521 is known to promote bone development, our results suggest that it acts as a critical switch in the commitment decision between the adipogenic and osteogenic lineages.